2020
DOI: 10.3201/eid2609.200562
|View full text |Cite
|
Sign up to set email alerts
|

Oxacillinase-181 Carbapenemase-Producing Klebsiella pneumoniae in Neonatal Intensive Care Unit, Ghana, 2017–2019

Abstract: We sequenced 29 carbapenemase-producing Klebsiella pneumoniae isolates from a neonatal intensive care unit in Ghana. Twenty-eight isolates were sequence type 17 with bla OXA-181 and differed by 0–32 single-nucleotide polymorphisms. Improved surveillance and infection control are needed to characterize and curb the spread of multidrug-resistant organisms in sub-Saharan Africa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 11 publications
1
16
0
Order By: Relevance
“…The OXA-181-encoding gene was first reported in 2007 and was subsequently identified in several countries, including its recent detection in Ghana [ 15 , 16 , 33 ]. It is mainly found in E. coli and K. pneumoniae strains with an increasing prevalence [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The OXA-181-encoding gene was first reported in 2007 and was subsequently identified in several countries, including its recent detection in Ghana [ 15 , 16 , 33 ]. It is mainly found in E. coli and K. pneumoniae strains with an increasing prevalence [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Labi and colleagues revealed a significant proportion of OXA-181-producing Klebsiella spp . among a neonatal population in a tertiary hospital in Ghana [ 15 , 16 ]. This finding suggests that the prevalence of bla O XA-181 is underreported in the general population, as most clinical laboratories are not equipped for its detection.…”
Section: Introductionmentioning
confidence: 99%
“…All the used reference genomes had average nucleotide identity ≥95% to our isolates as identified by fastANI (22). BacDist is an in-house developed workflow which was also used in other microbial genomics studies (23,24). BacDist is a Snakemake workflow (25) which first performs variant calling with Snippy 4 (26) using minimum read mapping quality of 50, minimum read coverage of 10, and minimum fraction of reads supporting the variant of 0.5 for each sample from the submitted sample group.…”
Section: Patient-to-patient Transmission Identificationmentioning
confidence: 99%
“…Treatment of infections caused by carbapenem-resistant pathogens is quite a big challenge in industrialized countries and almost impossible for health systems with limited resources [ 9 , 10 , 11 ]. Of great concern are carbapenemase-producing A. baumannii , P. aeruginosa and Enterobacterales [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%